Intraoral scanners in children: evaluation of the patient perception, reliability and reproducibility, and chairside time ¿A systematic review - Serrano Velasco, Diego; Martin Vacas, Andrea; Paz Cortés, Marta Macarena; Giovannini, Giovanni; Cintora López, Patricia; Aragoneses, Juan Manuel (My University, 2024)
Purpose: The aim of this systematic review is to evaluate the perception of the patient, the chairside time, and the reliability and/or reproducibility of intraoral scanners for full arch in pediatric patients. Methods: A data search was performed in four databases (Medline-Pubmed, Scopus, ProQuest and Web of Science) in accordance with the PRISMA 2020 statements. Studies were classified in three categories (patient perception, scanning or impression time and reliability and/or reproducibility). The resources, the data extraction and the quality assessment were carried out independently by two operators. The variables recorded were population characteristics, material and methods aspects and included country, study design and main conclusion. A quality assessment of the selected studies was performed with QUADAS-2 tool, and Kappa-Cohen Index was calculated to analyze examiner agreement. Results: The initial search obtained 681 publications, and finally four studies matching inclusion criteria were selected. The distribution of the studies in the categories was three for the analysis of the patient¿s perception and scanning or impression time; and two items to assess the reliability and/or reproducibility of intraoral scans. All included studies have a repeated measures¿transversal design. The sample size ranged between 26 and 59 children with a mean age. The intraoral scanners evaluated were Lava C.O.S, Cerec Omnicam, TRIOS Classic, TRIOS 3-Cart and TRIOS Ortho. The quality assessment of the studies using QUADAS-2 tool revealed a low risk of bias while evaluating patient perception, but an unclear risk of bias in the analysis of accuracy or chairside time. In relation to the applicability concerns, the patient selection was of high risk of bias. All studies agreed that the patient perception and comfort is better with intraoral scanners in comparison with the conventional method. The accuracy or reliability of the digital procedure is not clear, being clinically acceptable. In relation with the chairside time, it depends on the intraoral scanner, with contradictory data in the different analyzed studies. Conclusion: The use of intraoral scanners in children is a favorable option, finding a significantly higher patient perception and comfort with intraoral scanners compared to the conventional impression method. The evidence for reliability or reproducibility is not strong to date, however, the differences between the intraoral measurements and the digital models would be clinically acceptable. KEYWORDS intraoral scanner, digital flow, orthodontic, dental practices, pediatric dentistry